INFLUENCE OF TEACHERS’ ATTITUDE ON IMPLEMENTATION OF LANGUAGE OF INSTRUCTION POLICY. - Omweri, Martha Nyaboke; Juliet, Dr.Mugo,W. (IJRDO- Journal of Educational Research, 2017)
The purpose of the study was to investigate on implementation of the language of instruction policyin pre-unit and lower primary classes in Kasarani, Nairobi County, Kenya. The need to carry outthe study arose from the growing concern by various researchers that using the language of thecatchment area (LOCA) or mother tongue (MT) as a medium of instruction in lower primaryclasses had been displaced by English. This is in spite of the research findings that language of thecatchment area is crucial to the learning process. Specifically the purpose of the study was todetermine the teachers’ attitude on the implementation of language of instruction policy in preunitand lower classes and suggest interventions to enhance its implementation. The researcheradopted a descriptive research design, using the survey method. All the l50 lower primary schoolswithin the division, their head teachers/directors, 600 class teachers and 900 parents formed thetarget population of the study. The research was carried out on a sample of 45 (30%) primaryschools which were randomly selected according to strata, their head teachers, 90 teachers and asimilar number of parents. Data was collected using questionnaires and interview schedules. Priorto the study, piloting was conducted in five schools (two public and three private). Bothquantitative and qualitative research methods were used to analyze data. Specifically, quantitativedata was analyzed using descriptive analysis and data exploration. Preliminary reports andconclusions were based on descriptive statistics mainly frequencies and percentages and presentedusing charts, figures and text. Qualitative data were organized in themes and reported accordingto the research questions. Language of instruction determines the quality of education andtherefore should be a language which is understandable to both learners and teachers. The studyrevealed that although majority of teachers were aware of the language policy and supported theuse of language of catchment area for instruction, they were not using it because they found itchallenging to use to teach all subjects. Some of the suggestions made for intervention included:stepping up awareness of this policy to parents and teachers, training of teachers and in-servicing